2020
DOI: 10.3390/genes11070750
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Multiple Transgene Fragments in a Mouse Model of Gene Doping Based on Plasmid Vector Using TaqMan-qPCR Assay

Abstract: The World Anti-Doping Agency has prohibited gene doping in the context of progress in gene therapy. There is a risk that the augmentation of genes using plasmids could be applied for gene doping. However, no gold standard method to detect this has been established. Here, we aimed to develop a method to detect multiple transgene fragments as proof of gene doping. Firstly, gene delivery model mice as a mimic of gene doping were created by injecting firefly luciferase plasmid with polyethylenimine (PEI) i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Our previous studies have shown that whole-blood DNA contains high levels of viral genome DNA fragments as direct proof [5][6][7]; therefore, we performed the TaqMan qPCR assay with whole-blood DNA. For detection of direct proof of gene doping in wholeblood DNA in the short-and long-term experiments using the TaqMan qPCR assays, the primers and TaqMan probes were designed to target the EPO gene (2 types), TkpA (thymidine kinase polyA from herpes simplex virus), hexon (major virus capsid protein from adenovirus), and CMVp (cytomegalovirus promoter) to ensure specific amplification of the rAdV-hEPO genome using Primer-BLAST (NIH National Library of Medicine, Bethesda, MD, USA).…”
Section: Taqman Qpcr Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have shown that whole-blood DNA contains high levels of viral genome DNA fragments as direct proof [5][6][7]; therefore, we performed the TaqMan qPCR assay with whole-blood DNA. For detection of direct proof of gene doping in wholeblood DNA in the short-and long-term experiments using the TaqMan qPCR assays, the primers and TaqMan probes were designed to target the EPO gene (2 types), TkpA (thymidine kinase polyA from herpes simplex virus), hexon (major virus capsid protein from adenovirus), and CMVp (cytomegalovirus promoter) to ensure specific amplification of the rAdV-hEPO genome using Primer-BLAST (NIH National Library of Medicine, Bethesda, MD, USA).…”
Section: Taqman Qpcr Assaymentioning
confidence: 99%
“…This list includes "gene doping" as a form of abuse of gene therapy technology. Therefore, our research group has been conducting research for more than five years to establish an examination method for gene doping [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that whole blood DNA contains high levels of viral genome DNA fragments as direct proof [5][6][7]; therefore, we performed the TaqMan qPCR assay with whole blood DNA. For the TaqMan qPCR assays to detect direct proof of gene doping in whole blood DNA in the short-and long-term experiments, the primers and TaqMan probes were designed to target the EPO gene (2 types), TkpA, Hexon, and CMVp to ensure specific amplification of the rAdV-hEPO genome using Primer-BLAST (NIH National Library of Medicine, Bethesda, MD, USA).…”
Section: Taqman Qpcr Assaymentioning
confidence: 99%
“…This includes "gene doping" as abuse of gene therapy technology. Therefore, our research group has been conducting research for more five years to establish an examination method for gene doping [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The primary method used to detect the presence of transgene sequences has been via the polymerase chain reaction (PCR) to amplify a transgene‐specific region of DNA extracted from an appropriate biological sample matrix (typically plasma or whole blood). Existing studies have explored real‐time qPCR, 6,7 droplet digital PCR , 8,9 microfluidic qPCR, 10 and massively parallel sequencing, 11,12 which all have their uses as screening and/or confirmatory methods. The quantitative nature of digital PCR and qPCR, coupled with a high specificity and sensitivity of the hydrolysis probe‐based reagents and instruments, makes them particularly suited to confirmatory investigations where limits of detection can be calculated.…”
Section: Introductionmentioning
confidence: 99%